Response of Root Exudates of Bruguiera gymnorrhiza (L.) to Exposure of Polycyclic Aromatic Hydrocarbons - Liu, Beibei; Wu, Lin; Pan, Pan; Li, Ruilong; Lin, Bigui (Frontiers in Environmental Science, 2022)
Root exudates play a pivotal role in the behaviors of polycyclic aromatic hydrocarbons (PAHs) in mangrove sediments, but the knowledge of how mangrove root exudates response to PAHs pollutants is limited. This study examined the root exudates of Bruguiera gymnorrhiza (L.) (B. gymnorrhiza) under exposure in phenanthrene, pyrene and benzo[a]pyrene solution through a 45 days hydroponic cultivation. The results showed that the root exudates of B. gymnorrhiza were mainly hydrocarbon compounds, and tartaric acid were the dominant low molecular weight organic acids (LMWOAs) in root exudates. Under PAHs stress, the proportion of hydrocarbon compounds in root exudates decreased, while the proportion of amide compounds increased, and the amounts of dissolved organic carbon, soluble total sugars, total organic acids and LWMOAs of root exudates all increased firstly and reached the maximum values at 15d, while after 45 days of exposure, the amount of root exudates had dropped. The degradation rates of PAHs followed the sequence of phenanthrene > pyrene > benzo [a] pyrene, and the presence of root exudates can significantly enhance the degradation of PAHs. The results illustrated that PAHs stress can significantly change the concentrations and species of root exudates. This study provides the scientific reference for understanding the ability of B. gymnorrhiza response to PAHs stress.